Enhancing Wheat Growth and Yield through Nano-Fertilizer Applications: A Study on “Triticum aestivum var. Shriram Super 252" - Bhutia, Tashi Choki; Donbiaksiam, Tabitha; Jyotsna, Nongmaithem; Ariina, M. M. Shulee (Innovations in Biological Science Vol. 10, 2024)
The present study explores about enhancing Wheat Growth and Yield through Nano-Fertilizer Applications. Nano plant growth regulators (PGRs) are a multifaceted field and have vast applications in all spheres of life but in agriculture the application and utility are limited. Nano fertilizers facilitate the slow and constant release of nutrients and, therefore, decrease the loss of nutrients and improve the efficiency of the use of nutrients. It releases multiple types of nutrients simultaneously and is effective for the growth and yield of Wheat. These nanoparticles have high reactivity, better catalytic surface, rapid chemical reaction, rapidly dispersible and adsorb abundant water. The present research was conducted on Wheat (Shriram super 252) at the agricultural experimental farm of Calcutta University, Baruipur, 24 Parganas (south), West Bengal, to study the effect of various nano PGRs on the growth and productivity of wheat. The experiment was laid out in a Randomized Complete Block Design with three replications. Ten Treatments (T) with various doses of nano PGRs were given along with nitrogen(N), phosphorus(P), and potassium(K). The treatments of the experiment are T1= control; T2 = NPK @ 100:50:50 and foliar spray of green Nano PGR @ 0.5ml L-1; T3 = NPK @ 75:30:30 and foliar spray of Yellow Nano PGR @ 0.5ml L-1; T4 = NPK @ 75:30:30 and foliar spray of Red Nano PGR @0.5ml L-1; T5 = NPK @ 75:30:30 and foliar spray of Green Nano PGR @ 1 ml L-1; T6 = NPK @ 75:30:30 foliar spray of Yellow Nano PGR @ 1 ml L-1; T7 = NPK @ 75:30:30 and foliar spray of red Nano PGR @ 1 ml L-1; T8 = NPK @ 75:30:30 and foliar spray of Green Nano PGR @ 1.5 ml L-1; T9 = NPK @ 75:30:30 and foliar spray of Yellow Nano PGR @ 1.5 ml L-1; T10 = NPK @ 75:30:30 and foliar spray of Red Nano PGR @ 1.5 ml L-1. Various treatments showed a positive impact on Wheat cultivation in comparison to control. In spite of the positive role of enhancing plant growth and yield by the nanoparticles, studies have emphasized the harmful nanoparticles' impacts on plants. All the yield attributing characters showed that the usage of different doses of green nano PGR through foliar application has positive effects compared to yellow and red nano PGR and the lowest was from control. Therefore, with the help of nano PGRs, it is reported that it maximizes crop yield, reduces crop failure, decreases agricultural waste, and improves environmental stress responses. It will also help farmers in using PGRs in precision agriculture making farming more sustainable and mitigating the effect of climate change on crops.